Relationship of personal hygiene with nutrition and morbidity profile: A study among primary school children in South Kolkata - Deb Soumya; Dutta Sinjita; Dasgupta Aparajita; Misra Raghunath (Wolters Kluwer Medknow Publications, 2010)
Background: Majority of the health problems affecting school children are preventable by promotion of hygienic practices through proper health education by the teachers, who are the first contacts. Objectives: The study was undertaken to find out the status of nutrition and personal hygiene among primary school children and their association with their varied morbidity profiles. Materials and Methods: A descriptive, observational, cross-sectional study was conducted in a primary school situated in the largest slum of Kolkata. Results: The participants included 103 boys and 81 girls, with a mean age of 6.2 years. The mean personal hygiene score of the girls (4.15 ± 0.98) was significantly higher than that of boys (3.2 ± 1.4) [P<0.05]. Most of the boys (54.37%) and girls (74.07%) were normally nourished as per the CDC growth chart. Over 70% of the children were suffering from one or more morbidities, the most common morbidity in both the sexes being pallor, followed by worm infestation. Personal hygiene scores were significantly higher (P<0.05) among those children who were normally nourished as well as those who did not suffer from any morbidity in the last 15 days. Conclusions: Care should be taken to improve the pitiable state of personal hygiene and poor sanitary practices of these school children through coordinated and concerted health education measures by teachers as well as parents.